Healing in the African Independent Churches in the era of AIDS In Botswana - Kealotswe, Obed N. (Missionalia: Southern African Journal of Mission Studies, 2001)
This paper examines the role played by the diagelo in the care of terminally ill patients in Botswana. Diagelo refers to the clinics or hospitals of the AICs. The patients studied are mainly those connected with the AIDS pandemic. The AICs have always been known as healing churches and many researchers have pointed out that healing is the major attracting factor to enrolment, recruitment and growth in AICs.
Free